A multi-proxy study of an extinct giant armadillo juvenile unveils the initial life of pampatheres (Cingulata: Xenarthra: Mammalia). (October 2022) - Avilla, Leonardo S.; Góis, Flávio; Soibelzon, Esteban; de Abreu, Gabriel Muniz; Rotti, Alline
Abstract: Fossilization of mammalian young is extremely rare, mainly due to the fragility of bones (smaller and less mineralized) and unfused sutures, which are difficult to preserve during fossil diagenesis. Here, we describe an unprecedented and very complete juvenile of a pampathere, an extinct lineage of Cingulata (Xenarthra). The fossil comprises parts of the skull, mandible, and osteoderms from most regions of the armor, which were exhumed in association at the Gruta do Urso cave, Brazilian Amazon region. Taxonomic analysis of osteoderms and craniofacial features allowed the identification of this specimen as Holmesina . This individual of Holmesina has most of its cranial sutures unfused or in a very initial stage of fusion, and the osteoderms are under mineralized and poorly developed, suggesting a juvenile ontogenetic stage, probably a lactating individual. Although Holmesina is a common South American megafauna representative, little is known about its biology and even less about its initial life. Based on the taphonomic aspects of the fossil, it was buried at the same place of death; but before, its carcass was partially consumed. This study brings valuable information on the earlier stages of anatomy and paleobiology of native extinct South American megafauna. Highlights: The first newborn pampathere reported is represent by associated fossil elements of skull, mandible and several osteoderms. The pampathere carcass studied here was partially consumed before it was buried at the same place of its death. New information on the biology of the initial life of pampatheres, an enigmatic lineage of South American megafaunal mammals.